Corporate naming from a branding perspective: an analysis of naming criteria applied to company names - Olivares-Delgado, Fernando; Rodríguez-Valero, Daniel; Pinillos-Laffón, Alberto; Benlloch Osuna, María Teresa (iManagement&Tourism, 2024)
This article analyses the views of branding professionals on the types of brand names for companies. Brand naming is an important part of corporate branding that is hardly addressed from an academic perspective. The few works on naming deal with products or services, but not with companies. Based on personal in-depth interviews and semistructured questionnaires with renowned and prestigious experts from the professional branding sector, the relevance of common naming criteria for corporate brand names is measured. It is found that certain naming criteria seem to be more appropriate depending on the sector of activity of the company or the family or non-family character of the company. It is also found that their view of naming methods depends on their academic background and the specific professional field of activity in relation to brand management (design, advertising, marketing, linguistics or law, among others).
Keywords: Corporate name; Brand name; Family business; Brand management; Naming; Branding; Nome corporativo; Nome de marca; Empresa familiar; Gestão de marcas; Denominação; Branding; Nombre corporativo; Nombre de marca; Empresa familiar; Gestión de marcas; Denominación; Branding